Adénome Pléomorphe Géant à Localisation Submandibulaire: À Propos d’un Cas - M., Moussa; Hy., Abba Kaka; Sa., Bancolé Pognon; A., Camara; S., Samuila; R., Sani (European Scientific Journal, ESJ, 2019)
Introduction: The pleomorphic adenoma is a benign tumor of the salivary glands. Its extra parotid locations are rare. The aim of this study is to describe the particular management of the pleomorphic adenoma in its unusual location. Observation: This patient was a 35 - year - old patient referred from Zinder Hospital for the management of tumefaction in the mandibular region that had been undergoing surgery for 10 years. The clinical and paraclinical examinations led to the conclusion of a pleomorphic adenoma of the submandibular gland, by imaging and confirmed by the anatomo-pathological examination of the surgical specimen, which measured 15x12x8cm following submandibulectomy with complete tumor resection. The follow-up was simple and no recurrence or malignant transformation was reported after a mean follow-up of one year. Conclusion: The extra-parotid localization of the pleomorphic adenoma is dominated by the submandibular gland. This localization stands out in its clinical and therapeutic peculiarities. Introduction: L’adénome pléomorphe est une tumeur bénigne des glandes salivaires. Ses localisations extra parotidiennes sont rares. L’objectif de ce travail est de décrire la prise en charge particulière de l’adénome pléomorphe dans sa localisation inhabituelle. Observation: Ils’agissait d’un patient de 35 ans, référé de l’Hôpital National de Zinder pour la prise en charge d’une tumeur de la région mandibulaire évoluant depuis 10 ans. Les examens cliniques et paracliniques avaient permis de conclure à un adénome pléomorphe de la glande submandibulaire, par l’imagerie et confirmé par l’examen anatomo-pathologique de la pièce opératoire qui mesurait 15x12x 8cm suite à la submandibulectomie avec résection tumorale complète. Les suites opératoires étaient simples et aucune récidive ni transformation maligne n’a été rapportée après un recul d’un an. Conclusion: La localisation extra-parotidienne de l’adénome pléomorphe est dominée par la glande submandibulaire. Cette localisation se distingue dans ses particularités cliniques et thérapeutiques.